Sex Education According to the Bible for Married Couples for Family Harmony - Linutama Setiyawan; Andreas Kurniawan; Ronald Rachmat; Raymond Hessel Stephen; Ferry Simanjuntak (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Currently, many family problems occur due to poor communication. If this is allowed to drag on, it can lead to divorce in the family. And if examined more deeply, married couples who want to divorce have serious problems in sexual relations between husband and wife. This research paper provides a solution for married couples to have good sex relations and have good communication to create a harmonious family. And the most appropriate solution is to provide sex education for married couples. Sex education provided must be accurate according to the Bible, described in detail, according to the needs of married couples, and answer all existing problems. The Church can facilitate sex education for married couples by opening discipleship classes. The Church as the body of Christ must solve married couples who are having problems becoming married couples who are harmonious in God.